Critical Analysis of Religion and Morality: An Investigation into Types of Morality's Dependence on Religion - Raham Sharaf; Sahar Kavandi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Great importance of two fields of religion and morality necessitates the study of their relation. Religion and morality contribute to each other in many ways. However, in some cases, religious and moral propositions seem to be incompatible. Therefore, profound philosophical research is required to investigate possible relations and conflicts of these two fields. Religion and Morality: An Investigation into Types of Morality's Dependence on Religion has studied these issues and since this work is used as a textbook for students of philosophy of morality and philosophy of religion in master's level, it should be critically analyzed. The method we have applied in this article is library research as well as analytic.  First, the necessity of this research has been pointed out. Next, this book has been analyzed in terms of its form, and its advantages and disadvantages have been mentioned. Later, the book has been investigated in terms of its content mentioning its advantages and disadvantages in this respect as well. Finally, some suggestions have been provided for the improvement of this work.